Class Management in Improving Student Learning Participation in Elementary School Madrasah in Indonesia - Baidowi, Ach.; Ali, Himad; Putri, Sari Nusantara (STAI Publisistik Thawalib Jakarta, 2024)
Effective classroom management is influenced by strong leadership, harmonious relationships, and adequate facilities. This study explores the planning and supervision processes to enhance student learning participation, despite existing shortcomings in facilities and teaching methods. The research method used is qualitative, through a literature review by collecting data from scholarly articles on Google, focusing on classroom management in Madrasah Ibtidaiyah, followed by a series of analyses and data conclusions. The results of this study indicate that a comprehensive and contextual approach to classroom management significantly enhances student learning participation in Madrasah Ibtidaiyah. By integrating strategies such as creating a conducive classroom climate, effective class organization, clear enforcement of rules, and the use of varied teaching methods, teachers can actively engage students and foster a supportive learning environment. This approach not only improves student motivation and interaction but also contributes to better academic outcomes. The findings highlight the importance of teacher involvement, class management, and positive teacher-student interactions as key factors in promoting active and meaningful learning participation. Conclusion: Classroom management in Madrasah Ibtidaiyah involves strategies, rules, motivation, and seating design to enhance student participation, interaction, and learning outcomes.